Talimogene laherparepvec (T‐VEC) in advanced melanoma: complete response in a heart and kidney transplant patient. A case report. (1st July 2019) - Ressler, J.; Silmbrod, R.; Stepan, A.; Tuchmann, F.; Cicha, A.; Uyanik‐Ünal, K.; Hoeller, C.
Summary: Talimogene laherparepvec (T‐VEC) is a intralesional oncolytic virotherapy, licensed in the European Union for locoregional advanced melanoma of American Joint Committee on Cancer stages IIIB, IIIC and IVM1a. Organ transplant recipients are currently excluded from all clinical trials dealing with immunotherapies due to the risk of transplant rejection. A 58‐year‐old white man with a history of heart and kidney transplantation in 2014 was diagnosed with melanoma (Breslow thickness 1·6 mm, stage pT2a) on the left arm in September 2015. In March 2016 he developed in transit metastases, and local therapy with a combination of topical imiquimod (5%) and cryotherapy of individual lesions was initiated. However, in November 2016 therapy was stopped following local progression of the metastases. An interdisciplinary decision to treat the patient with T‐VEC was taken. After 11 cycles of T‐VEC, the patient showed a complete response. As of June 2018, 11 months after the last treatment cycle of T‐VEC, the patient continues to be tumour free. The patient tolerated the therapy well with only mild adverse events and did not show any sign of graft rejection or loss of function of the transplanted organs. We conclude that T‐VEC can be a potentially effective and safe treatment in patients with a history of organ transplantation. Nevertheless, due to this special situation, the risks and benefits should always be discussed with an interdisciplinary tumour board.